Cantharidin Induces Apoptosis and Promotes Differentiation of AML Cells Through Nuclear Receptor Nur77-Mediated Signaling Pathway - Zanyang Yu; Li Li; Chengqiang Wang; Hui He; Gen Liu; Haoyue Ma; Lei Pang; Mingdong Jiang; Qianwei Lu; Pan Li; Hongyi Qi (Frontiers Media S.A., 2020)
BackgroundAcute myeloid leukemia (AML) is a hematopoietic malignancy characterized by uncontrolled proliferation and accumulation of myeloblasts in the bone marrow (BM), blood, and other organs. The nuclear receptors Nur77 is a common feature in leukemic blasts and has emerged as a key therapeutic target for AML. Cantharidin (CTD), a main medicinal component of Mylabris (blister beetle), exerts an anticancer effect in multiple types of cancer cells.PurposeThis study aims to characterize the anti-AML activity of CTD in vitro and in vivo and explore the potential role of Nur77 signaling pathway.Study Design/MethodsThe inhibition of CTD on cell viability was performed in different AML cells, and then the inhibition of CTD on proliferation and colony formation was detected in HL-60 cells. Induction of apoptosis and promotion of differentiation by CTD were further determined. Then, the potential role of Nur77 signaling pathway was assessed. Finally, anti-AML activity was evaluated in NOD/SCID mice.ResultsIn our study, CTD exhibited potent inhibition on cell viability and colony formation ability of AML cells. Moreover, CTD significantly induced the apoptosis, which was partially reversed by Z-VAD-FMK. Meanwhile, CTD promoted the cleavage of caspases 8, 3 and PARP in HL-60 cells. Furthermore, CTD obviously suppressed the proliferation and induced the cell cycle arrest of HL-60 cells at G2/M phase. Meanwhile, CTD effectively promoted the differentiation of HL-60 cells. Notably, CTD transiently induced the expression of Nur77 protein. Interestingly, CTD promoted Nur77 translocation from the nucleus to the mitochondria and enhanced the interaction between Nur77 and Bcl-2, resulting in the exposure of the BH3 domain of Bcl-2, which is critical for the conversion of Bcl-2 from an antiapoptotic to a proapoptotic protein. Importantly, silencing of Nur77 attenuated CTD-induced apoptosis, reversed CTD-mediated cell cycle arrest and differentiation of HL-60 cells. Additionally, CTD also exhibited an antileukemic effect in NOD/SCID mice with the injection of HL-60 cells into the tail vein.ConclusionsOur studies suggest that Nur77-mediated signaling pathway may play a critical role in the induction of apoptosis and promotion of differentiation by CTD on AML cells.